2018
DOI: 10.48550/arxiv.1811.00950
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Near-Linear Time Algorithm for n-fold ILPs via Color Coding

Abstract: We study an important case of ILPs max{c T x | Ax = b, l ≤ x ≤ u, x ∈ Z nt } with n • t variables and lower and upper bounds ℓ, u ∈ Z nt . In n-fold ILPs non-zero entries only appear in the first r rows of the matrix A and in small blocks of size s × t along the diagonal underneath. Despite this restriction many optimization problems can be expressed in this form. It is known that n-fold ILPs can be solved in FPT time regarding the parameters s, r, and ∆, where ∆ is the greatest absolute value of an entry in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Subsequent work. Jansen, Lassota, and Rohwedder [36] showed a near-linear time algorithm for n-fold IP, which has a slightly better parameter dependence but slightly worse dependence on n when compared with our algorithms, and only applies to the case of (ILP) while our algorithm also solves (IP) and generalizes to tree-fold IP. Knop, Pilipczuk, and Wrochna [44] gave lower bounds for (ILP) with few rows and also (ILP) parameterized by td D (A); our lower bound of Theorem 114 generalizes their latter bound.…”
Section: Type Of Instancementioning
confidence: 79%
See 2 more Smart Citations
“…Subsequent work. Jansen, Lassota, and Rohwedder [36] showed a near-linear time algorithm for n-fold IP, which has a slightly better parameter dependence but slightly worse dependence on n when compared with our algorithms, and only applies to the case of (ILP) while our algorithm also solves (IP) and generalizes to tree-fold IP. Knop, Pilipczuk, and Wrochna [44] gave lower bounds for (ILP) with few rows and also (ILP) parameterized by td D (A); our lower bound of Theorem 114 generalizes their latter bound.…”
Section: Type Of Instancementioning
confidence: 79%
“…Previous best run time Our result n-fold a O(r st +st 2 ) n 3 L [28] a O(r 2 s+r s 2 ) (nt) 2 log 3 (nt) + R(A, L) Cor 91 a O(r 2 s+r s 2 ) (nt) log(nt)L Cor 91 n f1(a,r,s,t ) [11] t O(r ) (ar ) [42] (ars) O(r 2 s+s 2 ) (nt) log 6 (nt)L [36] 2-stage stochastic f 2 (a, r , s)n 3 L [49] f 3 (a, r , s)n 2 log 5 n + R(A, L) Cor 93 f 3 (a, r , s)n log 3 nL Cor 93 f 3 (a, r , s)n 2 log nL [40] Tree-fold f 4 (a, r 1 , . .…”
Section: Type Of Instancementioning
confidence: 99%
See 1 more Smart Citation
“…Eisenbrand et al [10] independently (and using slightly different techniques) arrive at the same complexity of N -fold IP as our Theorem 2. Jansen et al [20] have shown a near-linear time algorithm for N -fold IP with linear objectives. Their approach is relevant to implementations of an FPT algorithm for N -fold IP, however due to our approach of using existing ILP solvers as a subroutine we do not exploit it.…”
Section: Related Workmentioning
confidence: 99%
“…For each generated instance we run the iterative algorithm for various choices of the augmentation strategy Γ ∈ {Γ any , Γ best , Γ 2-apx , Γ 5-apx , Γ 10-apx } and the tuning parameter g 1 . The main parameters are thus gc_values A list of integers, by default [4,8,12,20,30,40,50,75,100], corresponding to choices of g 1 .…”
Section: Common Parametersmentioning
confidence: 99%